Peningkatan Hasil Belajar Siswa dengan Penerapan Model Problem Based Learning (PBL) pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan Kelas V SD Negeri 64 Banda Aceh - Noviyanti, Inda Mutia; Tursinawati; Herdiana (Mozaic : Islam Nusantara, 2025)
The research aims to improve student learning outcomes by using the PBL model in Pancasila and Citizenship Education subjects. This research is a Classroom Action Research model by Kemmis and Mc. Taggart. The research method used includes four stages, namely planning, action, observation and reflection. The subjects of this research were 16 class V students at SD Negeri 64 Banda Aceh in the odd semester of the 2023/2024 academic year, consisting of 9 boys and 7 girls. The data collection techniques used were written tests, observation and documentation. The data collection instruments used were diagnostic assessment, pretest and posttest, observation sheets, and documents. The data analysis technique used is quantitative descriptive. Based on the research, the results of student evaluations, which initially had an average score of 63% in the pre-cycle, experienced an increase in the average score in the first cycle by 67% and in the second cycle the average score was 81%. This shows an increase in learning outcomes for class V students at SD Negeri 64 Banda Aceh by using the PBL learning model which is characterized by student activity.